2002
DOI: 10.1039/b200674j
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of palladium in polyurea microcapsules

Abstract: An interfacial polymerisation approach is adopted to encapsulate palladium(II) acetate and palladium nanoparticles in polyurea microcapsules for use in catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(116 citation statements)
references
References 10 publications
1
115
0
Order By: Relevance
“…These are most clearly seen in the spectra of the ENCAT™ 30 sample at 2.827, 2.83, and 2.836 keV. The latter of these can also be seen to become more prominent after heating in ethanol/water to 350 K. These features correspond closely to Cl bound to Na on ClO 4 , ClO 3 , and ClO 2 forms, [34] implying that some of the chlorine retained is associated with residual levels of Na (arising from the use of sodium lignosulphate in polymer encapsulation process [1]) and that as a function of catalyst treatment the levels of these species can augment within the catalyst.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…These are most clearly seen in the spectra of the ENCAT™ 30 sample at 2.827, 2.83, and 2.836 keV. The latter of these can also be seen to become more prominent after heating in ethanol/water to 350 K. These features correspond closely to Cl bound to Na on ClO 4 , ClO 3 , and ClO 2 forms, [34] implying that some of the chlorine retained is associated with residual levels of Na (arising from the use of sodium lignosulphate in polymer encapsulation process [1]) and that as a function of catalyst treatment the levels of these species can augment within the catalyst.…”
Section: Discussionmentioning
confidence: 83%
“…It seems these Cl containing species may become encapsulated with the Pd and are not reliably removed by subsequent washing procedures. EDX (see supplemental data) also shows that Na and S (from sodium lignosulfonate used in the original preparation [1]) may also be trapped and, in the former case, the Cl K-edge XANES provides evidence that this can also subsequently form NaClO x species though reaction with some of the retained Cl.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Today, rather few works have been published using Pd-NPs in ILs as catalyst in this reaction. (Pathak et al, 2000;Ramarao et al, 2002;Gopidas et al, 2003;Narayanan & ElSayed, 2003;Pittelkow et al, 2003;Kim et al, 2004;Liu et al, 2004;Fernandez et al, 2007;Durand et al, 2008) For example, Calo and Nacci reported on Pd-NPs in tetraalkylammonium ILs, starting from Pd(OAc) 2 in the presence of TBAA at 90 °C, which were used as precursor for the coupling of aryl halides (Scheme 5; entry 6, Table 1 Interestingly, with tetrabutylammonium hydroxide as base, the catalytic efficiency increased significantly, thus, the reaction was performed even under milder conditions. This can be explained by the elevated concentration of tetraalkylammonium in water, contributing through partitioning equilibrium, keeping the concentration of the cations in the IL constant.…”
Section: Suzuki-miyaura Reactionmentioning
confidence: 99%